Erythromycin Restores Osteoblast Differentiation and Osteogenesis Suppressed by Porphyromonas gingivalis Lipopolysaccharide - Hikaru Tamura; Tomoki Maekawa; Hisanori Domon; Kridtapat Sirisereephap; Toshihito Isono; Satoru Hirayama; Takumi Hiyoshi; Karin Sasagawa; Fumio Takizawa; Takeyasu Maeda; Yutaka Terao; Koichi Tabeta (MDPI AG, 2023)
The macrolide erythromycin (ERM) inhibits excessive neutrophil accumulation and bone resorption in inflammatory tissues. We previously reported that the expression of developmental endothelial locus-1 (DEL-1), an endogenous anti-inflammatory factor induced by ERM, is involved in ERM action. Furthermore, DEL-1 is involved in the induction of bone regeneration. Therefore, in this study, we investigated whether ERM exerts an osteoblastogenic effect by upregulating DEL-1 under inflammatory conditions. We performed in vitro cell-based mechanistic analyses and used a model of Porphyromonas gingivalis lipopolysaccharide (LPS)-induced periodontitis to evaluate how ERM restores osteoblast activity. In vitro, P. gingivalis LPS stimulation suppressed osteoblast differentiation and bone formation. However, ERM treatment combined with P. gingivalis LPS stimulation upregulated osteoblast differentiation-related factors and Del1, indicating that osteoblast differentiation was restored. Alveolar bone resorption and gene expression were evaluated in a periodontitis model, and the results confirmed that ERM treatment increased DEL-1 expression and suppressed bone loss by increasing the expression of osteoblast-associated factors. In conclusion, ERM restores bone metabolism homeostasis in inflammatory environments possibly via the induction of DEL-1.